2021
DOI: 10.3390/ma14123434
|View full text |Cite
|
Sign up to set email alerts
|

Towards Enhancing the Potential of Injection Molding Tools through Optimized Close-Contour Cooling and Additive Manufacturing

Abstract: This work deals with the parametric optimization of the position and form of a conformal cooling used in the injection molding industry. Based on a literature survey, an optimization routine concerning the parameter optimization of cooling system designs was developed and implemented with the help of the software package Moldflow. The main objective of the optimization is to reduce the cooling time; the second is to obtain an optimized homogeneous temperature distribution over the complete tool surface. To ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Polyvinyl chloride (PVC) is used in the test. Shrinkage of this plastic material is 2 % with a density of 1.3-1.7 g/cm 3 and 212 °C melting temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyvinyl chloride (PVC) is used in the test. Shrinkage of this plastic material is 2 % with a density of 1.3-1.7 g/cm 3 and 212 °C melting temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The paper [3] suggested that one of the most costly and time-consuming phases in the new product development is the creation of production components and prototyping production tools. When temperature distribution is homogeneous, the cycle time from processing to demolding will be less and the production rates will be higher.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Injection molds were cooled by creating a straight drilled channel in the mold; but, that channel does not provide uniform and efficient cooling since it does not conform to the shape of the mold [6] . The conventional cooling approach faced difficulties in achieving consistent temperature distribution, resulting in longer cycle times due to the implementation of cooling circuits with straight drilled or milled channels [7][8][9] . In recent days, the Conformal Cooling Channel (CCC) has been frequently used in the injection molding process since it has more benefits than the conventional cooling channel [5] .…”
Section: Introductionmentioning
confidence: 99%